Pengembangan Fukien Ikan Kembung Banjar dengan Substitusi Tepung Talas Belitung (Xanthosoma sagittifolium): Analisis Sensori, Preferensi Konsumen, dan Rintisan Usaha - Wahyu Pamungkas; Handoko Handoko; Mutia Vanessia; Annis Kandriasari; Efrina Efrina (STKIP PGRI SITUBONDO, 2025)
This study aims to evaluate the sensory quality, consumer acceptability, and business feasibility of a novel fukien product made from Banjar mackerel and partially substituted with Belitung taro flour (Xanthosoma sagittifolium), named